A DOUBLE BLIND PHASE III STUDY OF ESAXERENONE (CS-3150) COMPARED TO EPLERENONE IN PATIENTS WITH ESSENTIAL HYPERTENSION (ESAX-HTN STUDY). (June 2018) - Ito, S.; Ito, H.; Rakugi, H.; Okuda, Y.; Yoshimura, M.; Yamakawa, S.
Abstract : Objective: ESAX-HTN study is a randomized, double-blind phase III study of esaxerenone (CS-3150), a novel non-steroidal mineralocorticoid receptor blocker, compared to eplerenone in patients with essential hypertension. The primary objective is to confirm non-inferiority of antihypertensive effect of esaxerenone 2.5 mg once daily compared to eplerenone 50 mg once daily. The secondary objective is to confirm superiority of antihypertensive effect of esaxerenone 5 mg/day as compared to 2.5 mg/day. Design and method: 1001 subjects with essential hypertension (sitting systolic blood pressure (sSBP): 140– < 180mmHg, diastolic blood pressure (sDBP): 90– < 110mmHg, 24-h blood pressure (BP) by ABPM: > 130/80mmHg) from 42 sites in Japan were enrolled in the study. Subjects were assigned to one of 3 groups (n = 330/group), and received 2.5 mg/day, 5 mg/day of esaxerenone, or 50 mg/day of eplerenone. Treatment period lasted 12weeks following 4-week washout period. Efficacy was assessed by monitoring trough sSBP/sDBP, and 24-h BP. Safety was assessed by monitoring serum potassium changes from baseline, and the occurrence of adverse events. Primary efficacy endpoint was changes of trough sSBP/sDBP from the baseline at the end of treatment. Results: Changes of sSBP/sDBP from the baseline were −13.7/−6.8mmHg in 2.5 mg of esaxerenone, −16.9/−8.4mmHg in 5 mg of esaxerenone and −12.1/−6.1mmHg in 50 mg of eplerenone. Non-inferiority of 2.5 mg esaxerenone to 50 mg eplerenone was confirmed in antihypertensive effect in the analysis with per protocol set. Superiority of 5 mg esaxerenone in sSBP/sDBP to 2.5 mg esaxerenone was confirmed in analysis with full analysis set (all p < 0.001). Similarly, mean 24-h SBP/DBP changes showed non-inferiority of 2.5 mg esaxerenone to 50 mg eplerenone, and 5 mg esaxerenone lowered mean 24-h SBP/DBP to a significantly greater extent as compared with 2.5 mg esaxerenone (p < 0.0001). Compared with 50 mg eplerenone, both doses of esaxerenone were well tolerated. No-dose dependent hyperkalemia (> = 5.5mEq/L) was observed in esaxerenone groups, and most were transient and recovered without any treatment. Conclusions: A novel non-steroidal mineralocorticoid receptor blocker esaxerenone showed good efficacy profiles on antihypertensive effect without significant safety concerns in essential hypertensive patients.